Effectiveness of Intelligent Financial Transformation on Cost Control of Construction Companies in Shandong, China - Cao, Xue (International Journal of Computer Science and Information Technology, 2025)
This study investigates the effectiveness of intelligent financial transformation in enhancing cost control among construction companies in Shandong, China. Using a qualitative research design, data were gathered through semi-structured interviews with fifteen financial managers, project accountants, and executives from various construction firms actively utilizing intelligent financial systems. Thematic analysis of the interview responses identified five themes: real-time cost monitoring and control, error reduction and financial accuracy, improved financial reporting and forecasting, enhanced transparency and compliance, and process automation and efficiency. The findings reveal that the integration of intelligent financial systems significantly contributes to proactive cost control, reduces manual errors, improves financial oversight, and enhances operational efficiency. These systems not only support more accurate financial decision-making but also strengthen the companies’ competitive advantage in a complex construction market. The study concludes that intelligent financial transformation is a critical factor in modernizing cost control practices and ensuring financial sustainability within the construction industry.